2022
DOI: 10.3390/su14084420
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Pro-Environmental Behaviour in the Workplace

Abstract: The primary notion of sustainable development is to maintain a promising future for the planet and the next of kin by raising the awareness of sustainable development of people around the world. This study seeks to foster and enhance more sustainable behaviour in households, workplaces, schools, and higher educational institutions; previous research has placed increasing attention on the identification of factors of pro-environmental behaviour. Accordingly, this study aims to examine the elements influencing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 93 publications
4
38
0
3
Order By: Relevance
“…Fatmawati et al ( 7 ) also concluded in a study of EB among young people in Indonesia that the participants showed good attitudes, willingness, and behavioral SFE toward electricity-saving behavior. However, the findings of this study are consistent with the findings of Foster et al ( 40 ) on the pro-environmental behavior of 150 public officials in an organization in Terengganu. The possible reason for the inconsistent results is that the study respondents did not pay enough attention to EB itself, while the reason for the consistency with the results of Foster et al ( 40 ) study may be that more of their respondents were young people.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Fatmawati et al ( 7 ) also concluded in a study of EB among young people in Indonesia that the participants showed good attitudes, willingness, and behavioral SFE toward electricity-saving behavior. However, the findings of this study are consistent with the findings of Foster et al ( 40 ) on the pro-environmental behavior of 150 public officials in an organization in Terengganu. The possible reason for the inconsistent results is that the study respondents did not pay enough attention to EB itself, while the reason for the consistency with the results of Foster et al ( 40 ) study may be that more of their respondents were young people.…”
Section: Discussionsupporting
confidence: 92%
“…However, the findings of this study are consistent with the findings of Foster et al ( 40 ) on the pro-environmental behavior of 150 public officials in an organization in Terengganu. The possible reason for the inconsistent results is that the study respondents did not pay enough attention to EB itself, while the reason for the consistency with the results of Foster et al ( 40 ) study may be that more of their respondents were young people. According to Fatmawati et al ( 7 ), the younger group belonged to those with the lowest energy consumption rate and low attention to EB.…”
Section: Discussionsupporting
confidence: 92%
“…The GSC got all the employees to agree on the same things, which led to the company putting a green human resource management system [20]. The company will conduct an employee selection process to achieve performance [21].…”
Section: Green Strategy Consensus and Agro-food Company Performancementioning
confidence: 99%
“…Menggabungkan antara tipe kepribadian dengan lingkungan, diperoleh beberapa tipe yakni lingkungan ekstraversi "menarik" orang ke dalam tindakan dengan menekan ke arah keterlibatan dan interaksi. Kecerdasan untuk menjadi seorang pemimpin tidak hanya sebatas pada kecerdasan kognitif, tetapi juga kecerdasan emosional, dan kecerdasan spiritual [11]. Kecerdasan untuk memimpin terdiri dari kecerdasan kognitif, kecerdasan emosional, kecerdasan cultural, kecerdasan moral, kecerdasan digital, kecerdasan gender, dan kecerdasan global [11].…”
Section: Kepribadian Ekstraversiunclassified
“…Kecerdasan untuk menjadi seorang pemimpin tidak hanya sebatas pada kecerdasan kognitif, tetapi juga kecerdasan emosional, dan kecerdasan spiritual [11]. Kecerdasan untuk memimpin terdiri dari kecerdasan kognitif, kecerdasan emosional, kecerdasan cultural, kecerdasan moral, kecerdasan digital, kecerdasan gender, dan kecerdasan global [11].…”
Section: Kepribadian Ekstraversiunclassified